THE ROLE OF DIET IN SUPPORTING THE PHYSICAL HEALTH AND PHYSICAL DEVELOPMENT OF ADOLESCENTS IN INDONESIA - Syauki Billi Asdani; Dienda Malika Azzahra; Sri Wahyuni; Muhammad Ilham (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze the role of dietary patterns in supporting the physical health and development of adolescents in Indonesia. The research used a descriptive qualitative approach with literature study and thematic analysis. The results indicate that the nutritional status of Indonesian adolescents still faces a double burden of malnutrition, encompassing both undernutrition and overnutrition. Unbalanced dietary patterns, low intake of energy, protein, and fat, as well as insufficient fiber consumption, are the main contributing factors. Nutritional knowledge, body image, and family influence especially the role of mothers significantly affect dietary quality. It is concluded that holistic nutritional interventions and continuous education are essential to support optimal adolescent growth and development.